Pooh's grand adventure : the search for Christopher Robin - Talkington, Bruce; Kurtz, John, 1955-; Milne, A. A. (Alan Alexander), 1882-1956. (New York : Disney Press, 1997)
When Christopher Robin is nowhere to be found, Pooh and his friends undertake a perilous search for him, and learn they're smarter, braver, and more loyal than they ever dreamed they'd be. Christopher Robin is a very important person in the Hundred-Acre Wood, and he's Pooh's very best friend. So when Christopher Robin goes away to some awful-sounding place called "skull", his friends are worried. Until Christopher Robin describes just how much fun skull (school) can be! Full color.
"Based on the Pooh stories by A.A. Milne"--T.p. verso.
At head of title: Disney.
edited hb 2015-06-16
Keywords: Winnie-the-Pooh -- (Fictitious character); Winnie-the-Pooh -- (Fictitious character); Best friends; Best friends; Teddy bears; Teddy bears; Toys; Toys; Fiction; Fiction